Tasavvuf geleneğin’de af - Gök, Hülya (My University, 2013)
Af; insanın ferdi ve toplumsal boyutta diğer insanlarla kurduğu münasebetlerinde gerek psikolojik olarak tabiatını ve kişiliğini gerekse dinî açıdan olgun bir ahlâki yapıyı ifade etmektedir. Bu çalışmada affın faziletleri, tasavvuf geleneğinde uygulanan usul ve yöntemlerin af üzerine etkileri, aynı zamanda affın kişinin kâmil insan olma sürecine katkıları tespit edilmeye çalışılmıştır. Güzel ahlâktanımının içeriğini oluşturan af ile bağlantılı kavramlar araştırılmıştır. Af davranışı üzerinde yapılan bilimsel çalışmalarla birlikte diğer dinlerin bakış açıları da incelenmiştir. Tasavvuf, Af, Güzel ahlâk, Tasavvuf Eserleri

Forgiveness, in his established connections to other people in individual and social dimensions, expresses human's psychological nature and personality as well as the mature moral structure in religious perspective. In this study, the virtues of forgiveness, the effects of procedures and methods implemented in the tradition of sufism on forgiveness, and contributions of forgiveness to the process of being a mature human were tried to be determined. The concepts associated with forgiveness which constitute the content of good morals were examined. The scientific studies on the behaviour of forgiveness along with the perspectives of other religions were analyzed. Sufism, Forgiveness, GoodMorals, Sufism Works
Keywords: Dini Yaşam; İslam; Tasavvuf